A conceptual model of medical tourism service supply chain - Saliha Karadayi-Usta; Seyda SerdarAsan (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: Medical tourism service requires involvement of multiple parties from the service network, however medical tourism is not well studied from a supply chain management perspective. This study suggests a conceptual model of medical tourism service supply chain (MTSSC) to provide a clearer understanding of its nature, and defines its business processes. Design/methodology/approach: Triangulation which makes use of literature review, in-depth interviews, and expert evaluations was applied to develop and validate the suggested model. The proposed model is initialized based on the relevant literature. In-depth interviews were used to refine and finalize the model. Expert evaluations ensure the trustworthiness of the model and the business process definitions. Findings: The proposed model uses a nested process structure rather than a one-dimensional supply chain model, where the assistance company maintains an intermediary role between the patient and all the service providers (e.g. medical institutions, transportation, accommodation). Additionally, the conceptual model identifies seven business processes: service design, service recovery management, customer relationship management, supplier relationship management, demand management, capacity and resource management, and service delivery management. Practical implications: The results provide a better understanding of the MTSSC structure and processes, and a recognition of the MTSSC members. The process definitions give the members an idea about their roles in the service design and delivery in practice. Additionally, a better understanding of the system as a whole leads to better process development and control. MTSSC members may shape their organizations internally and supply chain-wide by considering this conceptual model. Moreover, the model acts as a basis for supply chain collaboration decisions. Originality/value: The conceptual model is built upon the theories and practice of medical tourism services, supply chain management, and service operations management. This study contributes to the theory of medical tourism services management by explaining the MTSSC concepts and business processes, and extends existing knowledge.
Keywords: 650; Medical tourism; medical tourism service supply chain; supply chain business processes; triangulation; conceptual model